2013
DOI: 10.2196/ijmr.2314
|View full text |Cite
|
Sign up to set email alerts
|

Does Socioeconomic Status Affect Patients’ Ease of Use of a Touch-Screen (iPad) Patient Survey?

Abstract: Socioeconomic disparities influence the usage rate of advanced communication technologies in Canada. It is important to assess all patient interactions with computers and electronic devices based on these socioeconomic differences. This project studied the ease of use of a touch-screen interface program for collecting patient feedback. The interface collected feedback on physicians’ communication skills, an important health concern that has been garnering more and more attention. A concurrent paper survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 4 publications
(3 reference statements)
3
22
0
Order By: Relevance
“…Use of such strategies would probably increase the follow-up rate among hazardous and harmful drinkers from the 22/30 (73%) observed here to 24/30 (80%) or higher, putting it into an acceptable range for a trial of this type. Our finding that most participants could easily self-administer the e-SBI using an iPad is consistent with the findings of a Canadian study in which most (318/348, 91.4%) patients indicated that the iPad was easy to use [55]. Our observation that some patients would benefit from having a stylus available is also consistent with the Canadian study, which reported “some of the older users…seemed to struggle to adapt to the sensitivity and responsiveness of the touch screen” [55].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Use of such strategies would probably increase the follow-up rate among hazardous and harmful drinkers from the 22/30 (73%) observed here to 24/30 (80%) or higher, putting it into an acceptable range for a trial of this type. Our finding that most participants could easily self-administer the e-SBI using an iPad is consistent with the findings of a Canadian study in which most (318/348, 91.4%) patients indicated that the iPad was easy to use [55]. Our observation that some patients would benefit from having a stylus available is also consistent with the Canadian study, which reported “some of the older users…seemed to struggle to adapt to the sensitivity and responsiveness of the touch screen” [55].…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that most participants could easily self-administer the e-SBI using an iPad is consistent with the findings of a Canadian study in which most (318/348, 91.4%) patients indicated that the iPad was easy to use [55]. Our observation that some patients would benefit from having a stylus available is also consistent with the Canadian study, which reported “some of the older users…seemed to struggle to adapt to the sensitivity and responsiveness of the touch screen” [55]. As 27/99 (27%) of our study participants did not have access to email (ie, did not have the option of emailing a copy of the feedback to themselves to read and reflect upon later), our decision not to provide printed copies of the personalized feedback may also be a limitation.…”
Section: Discussionsupporting
confidence: 90%
“…1 In a similar vein, one study suggested that age is generally unrelated to ease of use of tablet computers, 24 whereas another study found that ease of use decreased with age. 25 Clearly, more research is needed to examine the utility of tablet computers.…”
Section: Discussionmentioning
confidence: 99%
“…In‐depth interviews with 5 investigators representing large health care quality projects praised the flexibility and research potential of tablet computers but also noted that unfamiliarity with tablet computers may limit their utility . In a similar vein, one study suggested that age is generally unrelated to ease of use of tablet computers, whereas another study found that ease of use decreased with age . Clearly, more research is needed to examine the utility of tablet computers.…”
mentioning
confidence: 99%
“…Purposive sampling was used in the selection of children from middle class independent schools. This was to ensure that a sample population that potentially use more electronic devices, based on the socio-economic demographics of these households were accessed (Zarghom, Di Fonzo, & Leung, 2013). A sample size of 384 for large populations is sufficient to ensure approximately 5% error at a 95% confidence level (Chetty & Bhagwanjee, 1990).…”
Section: Design and Samplingmentioning
confidence: 99%